Staphylococcus aureus induces eosinophil cell death mediated by α-hemolysin. - Lynne R Prince; Kirstie J Graham; John Connolly; Sadia Anwar; Robert Ridley; Ian Sabroe; Simon J Foster; Moira K B Whyte (PLoS ONE, 2012)
Staphylococcus aureus, a major human pathogen, exacerbates allergic disorders, including atopic dermatitis, nasal polyps and asthma, which are characterized by tissue eosinophilia. Eosinophils, via their destructive granule contents, can cause significant tissue damage, resulting in inflammation and further recruitment of inflammatory cells. We hypothesised that the relationship between S. aureus and eosinophils may contribute to disease pathology. We found that supernatants from S. aureus (SH1000 strain) cultures cause rapid and profound eosinophil necrosis, resulting in dramatic cell loss within 2 hours. This is in marked contrast to neutrophil granulocytes where no significant cell death was observed (at equivalent dilutions). Supernatants prepared from a strain deficient in the accessory gene regulator (agr) that produces reduced levels of many important virulence factors, including the abundantly produced α-hemolysin (Hla), failed to induce eosinophil death. The role of Hla in mediating eosinophil death was investigated using both an Hla deficient SH1000-modified strain, which did not induce eosinophil death, and purified Hla, which induced concentration-dependent eosinophil death via both apoptosis and necrosis. We conclude that S. aureus Hla induces aberrant eosinophil cell death in vitro and that this may increase tissue injury in allergic disease.